Using climate change scenarios to assess high school students' argumentation skills. Issue 1 (2nd January 2017) - Dawson, Vaille; Carson, Katherine
Abstract: Background: Many international science curriculum documents mandate that students should be able to participate in argument, debate and decision-making about contemporary science issues affecting society. Termed socioscientific issues, these topics provide students with opportunities to use their scientific knowledge to discuss, debate and defend their decisions and to evaluate the arguments of their peers. Purpose: This study describes the development and trialling of scenarios based on the socioscientific issue of climate change. The scenarios required students to make and justify a decision and were designed to assess students' argumentation skills. Sample: A sample of 162 Year 10 students from five schools in Perth, Western Australia participated in this study. Design and methods: Recent media articles were reviewed to identify relevant contexts for scenarios related to climate change that could be used to develop and assess students' argumentation skills. In the first phase, students trialled scenarios about wind farms and hydrogen fuel buses using writing frames with scaffolding questions to generate as many reasons as possible to justify their decision. The responses were categorised into themes which were used to prepare a scoring rubric. In the second phase, students generated written arguments about the scenarios to support their decision. The arguments were analysed using both the scoring rubric developed from the first phase and Toulmin's argumentation pattern of claim, data, backing, qualifier and rebuttal. Results: Students' responses to the scaffolded questions were categorised into themes of agriculture, economy, energy, environment, human impact and ethical factors. The themes of economy and the environment predominated with ethical justifications cited infrequently. An analysis of the arguments generated revealed a majority of students' responses consisted of a claim and data with backings, qualifiers and rebuttals rarely provided. Conclusions: Scenarios about climate change socioscientific issues can be used by teachers to both develop and assess students' argumentation skills in classroom settings.